Karakteristik Genetik dan Fenotip Ayam Nunukan di Pulau Tarakan, Kalimantan Timur (THE PHENOTHYPIC AND GENETIC CHARACTERISTIC OF NUNUKAN CHICKEN OF TARAKAN ISLAND, EAST BORNEO) - Alwi, Muhammad; Sumantri, Cece; Darwati, Sri (Jurnal Veteriner, 2014)
Nunukan chicken is local chicken of Tarakan and Nunukan in East Borneo Province. It is a germplasmof East Kalimantan which have special characteristics. Due to its characteristic, the chicken extremelyneed to be conserved and develop. This study was conducted to find out more reliable data on thecharacteristics of nunukan chicken in Tarakan Island. It was done by directly observed and measuredfenotype traits of nunukan chicken. Sample used was mature chicken, with the total tnumber 211 birds.Fenotype qualitative traits of nunukan chicken was florid brown of feather basic colour, columbian offeather colour theme, golden of feather flickering, and solid of feather pattern. The other special traits islittle growth (even not growth) of wings and tail feather, and on immature chicken (age of 0-5 month)commonly primary feather not growth. There was 13 fenotype quantitative traits on male, and two onfemale chicken was different between location (sub district) on 20 traits. The number of nunukan chickenat Tarakan Island was about 940 birds, and 36,17% was mature chicken. The effective population totalwas 299 birds, highest effective population was in West Tarakan (162 birds) and lowest was in MidleTarakan (46 birds). The average of inbreeding increased 0.177%, highest was in Midle Tarakan (1,08%)and lowest was in West Tarakan (0,31). The population of nunukan chicken in Tarakan Island was specificof the fenotype characteristic.
Keywords: nunukan chicken, Tarakan island, fenotype trait